1999
DOI: 10.1016/s0014-5793(98)01612-3
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular processing of HIV‐1 envelope glycoprotein gp160 by human plasmin

Abstract: Cleavage of the envelope glycoprotein precursor gp160 of HIV-1 is a prerequisite for the infectivity of HIV-1, and occurs at least in part before gp160 reaches the cell surface. Kexin/subtilisin-related endopeptidases are proposed enzyme candidates for this intracellular processing. In this study, we reveal the possibility that plasminogen binds to the cell surface and part of gp160 escaping intracellular processing is cleaved by plasmin extracellularly. Plasmin cleaves gp160 precisely at the C-terminal argini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…1A). This is consistent with the previous report on gp160 cleavage by plasmin (61). However, when a Western blot of the 16-h plasmin digest was probed with the gp120-specific MAb, B12, it was clear that plasmin also digests gp120 into fragments, one of which is about 70 kDa (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1A). This is consistent with the previous report on gp160 cleavage by plasmin (61). However, when a Western blot of the 16-h plasmin digest was probed with the gp120-specific MAb, B12, it was clear that plasmin also digests gp120 into fragments, one of which is about 70 kDa (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Although plasmin could efficiently process the gp120-gp41 cleavage site, as has been previously reported (61), it also cleaved gp120 at a second site, most probably within the V3 loop. This renders its use impractical.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Several invasive gram-positive and gram-negative bacteria have shown the ability to interact with the host PLG system (6,13,19,37,73), a phenomenon that has been extended to viruses (22,38,60) and parasites (68) (23,41,46,47,69,74). In the case of spirochetes, the PAS was studied with several species of Borrelia and with Treponema denticola and was suggested to have an important role during infectiveness (14,16,21,35,58).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that several pathogens, including the spirochete Borrelia burgdorferi, bind PLG on the surface and convert it to plasmin by host activators (6,13,16,19,22,31,34,37,38,60,68,73); this binding promotes degradation of ECM components and is essential for dissemination of the bacteria through the host tissues, suggesting its role during infection and pathogenesis (12,14,15,28,37,58).…”
mentioning
confidence: 99%